Herder-related violence, agricultural work, and the informal sector as a safety net - Bloem, Jeffrey R.; Damon, Amy; Francis, David C.; Mitchell, Harrison (World Bank, 2023)
Violent conflict between nomadic herders and settled—mostly agricultural—communities in Nigeria occurs as both groups clash over the use of land and resources, in part, due to a changing climate. This paper uses panel data from 2010 through 2019 to study the labor responses of individuals to exposure to herder-related violence during the post-planting and post-harvest seasons. Specifically, it considers a “shadow of violence” channel, where recent exposure to a violent event alters labor-related responses to a subsequent event. Results find that in the post-planting season, exposure to a herder-related violent event leads to an increase in informal work for both men and women, a decrease in agricultural work for men, and an increase in total hours worked for women among households that have previously been exposed to herder-related violence in the preceding six months. The paper also considers two other specific forms for a “shadow of violence” channel—namely, raised tensions over open-grazing bans enacted in 2016 and 2017 within three states and a drastic peak in violence in the first half of 2018— and find similar results. Lastly, findings show how household exposure to violence can have so-called knock-on effects. Households exposed to herder-related violence in the previous post-planting season shift consumption and crop selling patterns in the post-harvest season. These findings highlight the gender-specific labor response to violence and document the role of the informal sector as a partial safety net for individuals in the presence of adverse shocks.